Rubicon of the Golden Horde » - T.F. Khaydarov (Золотоордынское обозрение, 2016)
The article deals with the natural-climatic and environmental factors in the history of the Golden Horde. From the very beginning of its existence the Jochid Ulus proved to be very dependent on the environment. Its existence as a major military and political union and an important element of the global economic system directly depended on recreational potential of the Lower Volga steppe biome in the recovery of the steppe’s original form. This could worsen the ecological situation both because of the active human impact on the ecology of the region, and as a consequence of climate change. Prudent economic policy of the Horde rulers during the favorable natural and climatic period allowed the Jochid ulus to become in the shortest time the center of attraction in the Black Sea-Caspian region. New Horde towns played a major role in this process. They represented mostly the enlarged nomadic camps with few fixed structures. Even after the development of economic and cultural relations along the Silk Road in the late 13th century and the subsequent economic recovery of the ancient urban centers in Central Asia, the Crimean and Bulgar uluses, new Horde towns of the Lower and Middle Volga regions and Western Siberia continued to bear the imprint of the nomadic settlements at a new stage. At the same time, signs of active construction of permanent structures emerged in these towns. Taking into account the urban achievements of eastern countries, these towns gradually became places of attraction for the urban districts and surrounding areas. The sharp level change of the Caspian, Azov and Aral Seas began in 1320. Along with an increase in seismic activity and climate instability, this change became a detonator of the catastrophic consequences for the Golden Horde. The epidemic (“Black Death”), demographic (famine) and political-military (“Great zamyatnya”) factors represented the Rubicon that the Jochid ulus could not cross. At the same time, remaining Golden Horde towns in the Crimean and Bulgar uluses had been able to become the centers of formation of a new political elite of the post-Horde Tatars.